SMM-маркетинг у діяльності виробників пива в Україні - Кузьо, Н. Є.; Косар, Н. С.; Kuzo, N. Ye.; Kosar, N. S. (Видавництво Львівської політехніки, 2024)
У сучасних умовах соціальні мережі є одним із найбільш важливих каналів про- сування бренду та комунікації з цільовою авдиторією. Аналіз відгуків споживачів у соцмережах, вивчення статистики та інших параметрів дає змогу зрозуміти, що подо- бається користувачам та що підприємствам-виробникам потрібно покращити. Проведені дослідження показали, що серед найбільших виробників пива активні маркетингові комунікації проводять ПрАТ “Карлсберг Україна“ та ПрАТ “Абінбев Ефес Україна”. Одночасно ПрАТ “Оболонь” та ТОВ “Перша приватна броварня” не надають достатньої уваги соціальним мережам, публікації інформації про реалізацію за- ходів соціально-відповідального бізнесу, що особливо важливо в умовах війни. Серед проаналізованих соціальних мереж “Фейсбук” та “Інстаграм” ПрАТ “Карлсберг Україна” переважає своїх основних конкурентів за величиною спільноти та загальною кількістю взаємодій, проте поступається ПрАТ “Абінбев Ефес Україна” за кількістю дописів та їх поширень. ПрАТ “Карлсберг Україна” є лідером серед конкурентів за величиною спільноти, кількістю відео та загальних переглядів у соцмережі “Ютуб”. ПрАТ “Абінбев Ефес Україна” не надає уваги цій соцмережі. У роботі розроблено заходи щодо активізації діяльності виробників пива у таких соціальних мережах, як “Фейсбук”, “Інстаграм”, “Ютуб”, подано рекомендовану тематику дописів.

Alcoholic beverage producers contribute significantly to state budget revenues. Among these beverages, beer holds a substantial share, often serving as a vital aspect of social interaction. To stimulate demand, beer producers engage in proactive marketing strategies. This article aims to examine current trends in the Ukrainian beer market, analyze the social media activities of major producers, and propose strategies for their enhancement. It has been established that military actions have had a negative impact on the markets of all goods, including the beer market, where demand and supply began to recover in the second half of 2022. However, there is fierce competition in the beer market. To strengthen their competitive positions, producers strive to build strong brands, introduce innovations, offer new product types, expand distribution networks and communication channels, engage in socially responsible business activities, and disseminate information about them using traditional and online communications. In today’s environment, social media is one of the most important channels for brand promotion and communication with the target audience. Analyzing consumer feedback on social media, studying statistics, and other parameters enable understanding what users like and what manufacturers need to improve. Research has shown that PrJSC “Obolon” and “Persha Pryvatna Brovarnya” Ltd do not pay sufficient attention to the social network Facebook, as evidenced by the low number of posts and interactions with consumers. PrJSC “Carlsberg Ukraine” surpasses these main competitors on this social network in terms of community size, number of posts, and total interactions, but lags behind PrJSC “Abinbev Efes Ukraine” in the number of posts and their shares. On Instagram, although PrJSC “Carlsberg Ukraine” has a small audience, it surpasses “Persha Pryvatna Brovarnya” Ltd in terms of community size and total interactions. The leader in this social network in terms of the number of posts is PrJSC “Abinbev Efes Ukraine”. PrJSC “Obolon” does not have its own page on the Instagram social network. Research has shown that PrJSC “Carlsberg Ukraine” is the leader among competitors in terms of community size, number of videos, and total views on the YouTube social network. PrJSC “Abinbev Efes Ukraine” does not pay attention to this social network. Measures have been developed to intensify the activities of beer producers in various social networks – Facebook, Instagram, and YouTube, and recommended topics for posts have been presented.
SMM marketing in the activities of beer producers in Ukraine
Keywords: ринок пива; виробники пива; фейсбук; інстаграм; ютуб; величина спільноти; кількість дописів; взаємодії із споживачами; beer market; beer producers; Facebook; Instagram; YouTube; community size; number of posts; interactions with consumers; 004.738.5; 339.138